The Efficacy of Collaborative Learning Assisted with Lapbook Media in Enhancing EFL Learners’ Reading Comprehension - Oktaviani, Ayu; Episiasi, Episiasi; Yulfi, Yulfi (Journal of Language and Literature Studies, 2026)
Reading comprehension remains one of the major challenges faced by English as a Foreign Language (EFL) learners, particularly in junior high school contexts where students often demonstrate limited engagement and difficulty in understanding texts. This study aimed to investigate the effectiveness of collaborative learning assisted with lapbook media in improving EFL learners’ reading comprehension and learning engagement. The research employed an explanatory sequential mixed-method design involving 34 eighth-grade EFL learners at a public junior high school. Quantitative data were collected through reading comprehension pre-test and post-test measurements, while qualitative data were obtained from structured classroom observations to explain the learning processes underlying students’ improvement. The quantitative findings revealed a significant improvement in students’ reading comprehension achievement, with the mean score increasing from 74.18 in the pre-test to 81.82 in the post-test. Statistical analysis indicated that collaborative learning assisted with lapbook media had a positive influence on learners’ reading comprehension performance. Qualitative results further demonstrated that the learning model enhanced students’ engagement, collaborative interaction, motivation, and strategic reading behaviors. The use of lapbook media enabled students to visually organize textual information, summarize ideas, and collaboratively construct meaning, thereby facilitating deeper comprehension and retention of reading materials. The integration of collaborative learning and lapbook media created an interactive and student-centered learning environment that supported both cognitive and social aspects of language learning. This study contributes pedagogical insight into the application of constructivist-based collaborative instruction combined with visual learning media in EFL reading classrooms. The findings suggest that lapbook-assisted collaborative learning can serve as an effective instructional strategy for improving reading comprehension among EFL learners.